2005
DOI: 10.1603/0013-8746(2005)098[0673:cooacd]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Competitive Outcomes of Aquatic Container Diptera Depend on Predation and Resource Levels

Abstract: Resources and predation are both known to be important in structuring communities; however the strength of one factor may be affected by the intensity of the other. This study used a fully crossed factorial experiment in laboratory microcosms to examine the ability of a predator, Corethrella appendiculata (Grabham), and basal resources (leaf litter) to differentially affect two competing species of mosquito prey. Increased resources resulted in shorter developmental time and increased survivorship, mass, and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
43
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 39 publications
(46 citation statements)
references
References 63 publications
3
43
0
Order By: Relevance
“…appendiculata compared to A. albopictus (Fig. 6), as shown by others (Griswold and Lounibos 2005c). Studies have shown that direct effects of predation (e.g., predator-mediated release from competition) (e.g., Morin 1981), as well as trait-mediated indirect effects of predation (e.g., morphology and behavior) (Werner and Anholt 1996;Relyea 2000) may reverse the outcome of competition.…”
Section: Sex-dependent Outcomessupporting
confidence: 73%
See 1 more Smart Citation
“…appendiculata compared to A. albopictus (Fig. 6), as shown by others (Griswold and Lounibos 2005c). Studies have shown that direct effects of predation (e.g., predator-mediated release from competition) (e.g., Morin 1981), as well as trait-mediated indirect effects of predation (e.g., morphology and behavior) (Werner and Anholt 1996;Relyea 2000) may reverse the outcome of competition.…”
Section: Sex-dependent Outcomessupporting
confidence: 73%
“…Studies have shown that direct effects of predation (e.g., predator-mediated release from competition) (e.g., Morin 1981), as well as trait-mediated indirect effects of predation (e.g., morphology and behavior) (Werner and Anholt 1996;Relyea 2000) may reverse the outcome of competition. In the current study, predator-mediated release from interspecific competition as well as behavioral differences among the prey in the presence of a predator may largely be responsible (Morin 1981;Werner and Anholt 1996;Griswold and Lounibos, 2005c).…”
Section: Sex-dependent Outcomesmentioning
confidence: 77%
“…Behavioral responses of A. albopictus to water-borne cues to risk of predation are either absent (Kesavaraju and Juliano 2004) or of much smaller magnitude than those of native O. triseriatus (Kesavaraju et al 2007a). This likely contributes to greater vulnerability of A. albopictus to predation by C. appendiculata (and to other predators like Toxorhynchites rutilus (order, Diptera; family, Culicidae) compared to O. triseriatus (Lounibos et al 2001;Griswold and Lounibos 2005a;Griswold and Lounibos 2005b).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that A. albopictus is more vulnerable to C. appendiculata predation than is O. triseriatus Lounibos 2005a, Griswold andLounibos 2005b;Kesavaraju et al 2007a), but follow up studies on how vulnerability affects distribution in the field were lacking. Our study shows that in natural container habitats like tree holes, C. appendiculata is more abundant than in artiWcial container habitats, and may be impeding dominance by A. albopictus.…”
Section: Discussionmentioning
confidence: 99%
“…The family Corethrellidae is closely related to the Culicidae with a similar life cycle including an aquatic larva and pupa followed by an adult, females of which typically feed on frog blood to gain nutrients for egg production. C. appendiculata larvae are predatory occupants of container habitats (Griswold andLounibos 2005, Kesavaraju et al 2007) and may be found at high densities in the Þeld (Lounibos 1983). The experimental advantages of this species include discrete prey allowing for easy measurement of food consumption, ability to be reared in large numbers, and lengthy development time, facilitating detectability of treatment effects.…”
mentioning
confidence: 99%